On the effectiveness of restorative justice in the ecocide crime - Babakhani, Erfan (Vilnius University Open Series, 2023)
This paper will review some concepts elaborated upon by restorative justice and reflect on how some of them can be put in with the context of the ecocide crime. It can be said that this crime, as the fifth most serious crime against global peace, is a new threat for a human’s life. The crime of ecocide, especially its governmental and corporate types, severely damages and destroys the environment, and in addition to the threat it poses to environmental security, ecocide undermines the foundations of economic and social security. The author used a descriptive-analytical approach and library resources to study the process of invention of the concept of ecocide as well as its essence in restorative justice thought. The present study tries to show that restorative justice applied to ecocide crime is a justice that provides environmental revitalisation-reparation. This novel vision will attempt to provide judicial actors insights regarding the role played by restorative policies to restore or sustain ecological functioning in the promotion of human rights, survival of environment, and the diminishment of social suffering.
Keywords: restorative justice; ecocide; environment; reparation